2017
DOI: 10.1080/02726351.2017.1313798
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of structure and electrical characteristics of lanthanum strontium manganite nanopowders with different Sr2+ ion concentrations

Abstract: Generally, the efficiency of solid oxide fuel cells (SOFCs) is heavily dependent on the electrocatalytic activity of the cathode toward the oxygen reduction reaction (ORR). In order to achieve a better cathode performance, LaxSr1-xMnO3 (LSM) nanopowders with different Sr 2+ ion contents varying from 0.2 to 0.8 have been synthesized using the co-precipitation method. The obtained nanoparticles were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and electrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…[55] It was shown that increasing Sr concentration up to x = 0.5 in LSM matrix for LSM-YSZ composites is advantageous for both electronic conductivity and polarization resistance. [5,[56][57][58] Nevertheless, normally, compositions ranging from x = 0.15 to x = 0.2 are chosen due to their mechanical suitability with YSZ. [58] Ananyev et al [59] also developed LSM-YSZ composite cathode for SOFC.…”
Section: Lsm-based Perovskite Materials As Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…[55] It was shown that increasing Sr concentration up to x = 0.5 in LSM matrix for LSM-YSZ composites is advantageous for both electronic conductivity and polarization resistance. [5,[56][57][58] Nevertheless, normally, compositions ranging from x = 0.15 to x = 0.2 are chosen due to their mechanical suitability with YSZ. [58] Ananyev et al [59] also developed LSM-YSZ composite cathode for SOFC.…”
Section: Lsm-based Perovskite Materials As Cathodementioning
confidence: 99%
“…[5,[56][57][58] Nevertheless, normally, compositions ranging from x = 0.15 to x = 0.2 are chosen due to their mechanical suitability with YSZ. [58] Ananyev et al [59] also developed LSM-YSZ composite cathode for SOFC. The oxygen isotope method was adopted to study the exchange kinetics with the oxygen gas phase.…”
Section: Lsm-based Perovskite Materials As Cathodementioning
confidence: 99%
“…Existem diferentes métodos de preparação de nanomateriais, os quais utilizam diferentes precursores, e consequentemente resultam em distintos tamanhos e morfologias de nanopartículas, bem como em diferentes propriedades funcionais. Desta forma, as nanopartículas de materiais perovskitas à base LaMnO 3 têm sido frequentemente sintetizadas por métodos tais como: sol gel (Wu et al, 2005), método de citrato (Choi et al, 2018), combustão (Turky et al, 2017), co precipitação (Turky et al, 2018) e síntese hidrotermal (Hehab et al, 2019) É bem conhecido que o controle do tamanho, forma e estrutura dos materiais nanométricos é de fundamental importância para suas aplicações da nanotecnologia. Recentemente, a produção de nanomateriais cerâmicos unidimensionais (nanofibras) tem atraído atenção por diversos pesquisadores, não somente pelos pequenos diâmetros (10-100 nm) das fibras, mas também por sua área superficial elevada, baixa densidade e estrutura porosa (Panda e Sahoo, 2013; Zhi et al, 2012).…”
Section: Introductionunclassified